“We” May Be in This Together, but We Are Not All Human and We Are Not One and the Same - Rosi Braidotti (Ecocene: Cappadocia Journal of Environmental Humanities, 2020)
There has never been a more urgent time to engage with the Environmental Humanities and the other Posthumanities. This engagement is creative as well as critical and it touches upon some fundamental issues within what I have called the posthuman convergence. That is the intersection of two concurrent but contradictory phenomena: the unprecedented technological developments that have also become known as the Fourth Industrial Revolution and the acceleration of the climate change emergency, also known as the Sixth Extinction. This complex intersection of events triggers multiple fractures, ethical dilemmas, affective perturbations, political concerns, and critical lines of inquiry. I have summarized them as the convergent critiques of Humanism on the one hand and the rejection of anthropocentrism on the other. This is neither a simple nor a harmonious intersection of critical lines, but rather an encounter fraught with painful contradictions and challenging problems.